Diets with biological silage of cornmeal improve the productive performance of river shrimp Cryphiops caementarius (Crustacea: Palaemonidae) - Gallardo-Carril, Juan (2020)
The aim was to evaluate diets with biological cornmeal silage in order to improve the productive performance of Cryphiops caementarius river shrimp. Shrimp were grown in 12 aquariums (55 L). Shrimp were randomly stocked (32 m-2) and fed diets containing 4.2%, 8.4% and 12.5% cornmeal silage and a control diet without silage. Experiment lasted 60 days. Physical, organoleptic and chemical quality of silage and the diets were analyzed at beginning. Silage had 8.57% protein; 16.49% total lipids; 1.45% fiber; 2.25% ash; 71.24% carbohydrates, and the pH was 4.40. Increase in level of corn silage (0% to 12.5%) in diets caused an increase in carbohydrates (38% to 47%) and a decrease in lipids (11% to 14%). Shrimp survival was similar (p > 0.05) between treatments (> 88%). Diet with 12.5% corn silage caused higher growth rates shrimp weight (p < 0.05) than those fed a diet without silage; although it was similar (p > 0.05) with those fed with 8.4% and 4.2% silage.